AB0017 Therapeutic effect of umbilical cord-derived mesenchymal stem cells transplantation in a mouse model of primary biliary cirrhosis. (15th June 2017) - Fan, J; Wang, Q; Feng, R; Yao, G; Tang, X; Sun, L
Abstract : Background: Primary biliary cirrhosis (PBC) is a cholestatic liver disease characterized by slowly progressive non-suppurative cholangitis with immune mediated destruction of intrahepatic bile ducts. Previous studies have shown beneficial effects of mesenchymal stem cells (MSCs) transplantation in many autoimmune diseases. However, few studies have focused on the effects of MSCs on PBC. Objectives: In our study, we investigated the therapeutic effect of umbilical cord-derived mesenchymal stem cells (UC-MSCs) transplantation in a well-defined mouse model of PBC and explored the potential mechanism. Methods: After 2OA-BSA-induced autoimmune cholangitis was created in C57BL/6 mice, cultured human UC-MSCs or a vehicle control was administered. Liver injury severity was assessed by clinical and histologic analysis. The immunity suppression effects and mechanism of UC-MSCs were tested. Results: UC-MSCs administration alleviated bile duct damage and intrahepatic inflammatory cell infiltration in C57BL/6 mice that had undergone 2OA-BSA immunization. Serum levels of ALT and ALP were significantly decreased. Also, UC-MSCs reduced the production of anti-mitochondrial autoantibodies (AMA) in PBC mice. UC-MSCs downregulated inflammatory cytokine, such as IFN-γ, TNF-α, IL-12 and IL-17A production both in peripheral blood and local liver. Notably, Infusion of UC-MSCs resulted in an increase in regulatory T cells (Tregs) in peripheral blood but a decrease of this kind of cells in liver tissues. Furthermore, UC-MSCs significantly suppressed Th1- and Th17-cell responses and these alternations could be detected in spleen, peripheral blood and liver in PBC mice. Conclusions: In summary, the current study shows that UC-MSCs based therapy has profound inhibitory effects on inflammatory responses and immunoregulatory effects both in local and systemic abnormalities in PBC. These findings also provide further evidence regarding the role of MSCs in the clinical trials of PBC. Disclosure of Interest: None declared